2011
DOI: 10.1371/journal.pone.0027513
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Transposable Element Derived Enhancers Using Chromatin Modification Profiles

Abstract: Experimentally characterized enhancer regions have previously been shown to display specific patterns of enrichment for several different histone modifications. We modelled these enhancer chromatin profiles in the human genome and used them to guide the search for novel enhancers derived from transposable element (TE) sequences. To do this, a computational approach was taken to analyze the genome-wide histone modification landscape characterized by the ENCODE project in two human hematopoietic cell types, GM12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…We found that not only are MIRs highly concentrated in predicted enhancers, but they also constitute a significant part of the core of genic enhancers; this analysis identified many more putative MIR-derived enhancers than previously reported [22,33]. These MIR-derived enhancers have cell-type specific chromatin profiles that are highly similar to those seen for canonical enhancers.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…We found that not only are MIRs highly concentrated in predicted enhancers, but they also constitute a significant part of the core of genic enhancers; this analysis identified many more putative MIR-derived enhancers than previously reported [22,33]. These MIR-derived enhancers have cell-type specific chromatin profiles that are highly similar to those seen for canonical enhancers.…”
Section: Introductionsupporting
confidence: 62%
“…And while MIRs are known to donate enhancers in a number of individual cases [21,22,33], these data show an even deeper relationship, namely that MIRs are substantially concentrated in enhancers genome-wide.…”
Section: Resultsmentioning
confidence: 99%
“…The evolutionary process by which TE sequences are subverted for novel function by the host genome is known as "exaptation" (de Souza et al 2013). There is extensive literature demonstrating that TEs have contributed repeatedly and profoundly to the evolution of genome structure and function through the insertion of preformed sequence elements, both at the level of genomic DNA, e.g., transcription factor binding sites (Johnson et al 2006), splice sites (Sela et al 2010), enhancer elements (Huda et al 2011b), and promoters (Huda et al 2011a), and at the level of RNA, e.g., microRNA genes (Spengler et al 2014), recognition elements (Piriyapongsa and Jordan 2007), and protein-coding domains (Bowen and Jordan 2007).…”
Section: Te Sequences Are Abundantly Found In Lncrna Exonsmentioning
confidence: 99%
“…First of all, a number of noncoding MIR sequences were found to be highly conserved, indicative of some functional, presumably regulatory, role (24). Later, it was shown that MIRs are enriched for open chromatin sites (25), encode regulatory RNAs (26), host gene promoters (27) and enhancers (28), and are also associated with tissue-specific expressed genes (29). Finally, and most importantly, MIRs are tRNA-derived SINEs (30) and their sequences include recognizable regulatory motifs, such as the promoter B-box element for Pol III binding, which are thought to be important for insulator activity.…”
Section: Significancementioning
confidence: 99%